Casting the light on cinema – how luminance and contrast patterns create meaning - Maszerowska, Anna (MonTi Monografías de Traducción e Interpretación, 2014)
The question of meaning creation has always been at the core of cross-disciplinary scholarly research. Considered from the cinematographic perspective, it inevitably evokes correlations with plot and dialogue. However, the conveyance of significance in films does not rely solely on the verbal channel, but also manifests itself in the visual layer, ranging from facial expressions, setting and locations, to directorial editing choices. Elevating the role of the how of film making, this article focuses on the influence of light and contrast patterns on the reading of cinema. In order to highlight their position in film text vocabulary and recognize their relevance in film translations and adaptations, this paper discusses the role of luminance patterns in active perception within motion pictures, explores their potential contribution to plot completion, and investigates the processes of filmic content hierarchization supported by light and contrast.